EFFECT OF DEPOSITION TIME AND MICROSTRUCTURE ON TRANSITION METAL MOLYBDENUM CHALCOGENIDES FOR PHOTOVOLTAIC APPLICATIONS - Anand, T.J.S.; Shariza, S.; Abd Razak, S.I.; Vedhi, C. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This paper highlights into the synthesis of semiconductor materials, specifically transition metal chalcogenide thin films and the characterization of the films to evaluate the suitability for application as a photoelectrochemical (PEC) / solar cell. Electrodeposition technique is used that aims to design a safe, cost-efficient and relatively simple method for synthesis of the transition metal chalcogenide thin film for potential applications as PEC / solar cell manufacturing industry. Transition Metal chalcogenide (MoX2) thin films were successfully electrodeposited on conductive glass substrates and metal substrates in which the deposition time for the thin films were set up to 30 minutes with an interval time of 5 minutes. The thin films were characterized for their compositional and morphological characteristics by energy dispersive X-ray (EDX) analysis and scanning electron microscope (SEM) respectively. Addition of selenium element increases the orientation of crystals in the films are formed. The suitability of the thin films for photoelectrochemical (PEC) / solar cell applications, optical and semiconducting parameters were analyzed. Films revealed it is of n-type nature with the Energy gap lying between 1.12 – 1.22 eV for the deposited films.